Akibat Hukum Akta Jual Beli Tanah yang dibuat oleh Pejabat Pembuat Akta Tanah tanpa Sepengetahuan Pemilik Tanah : (Studi Putusan Mahkamah Agung Nomor 3507 K/Pdt/2023) (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The Land Deed Official (Pejabat Pembuat Akta Tanah or PPAT) is a public official authorized to draw up deeds related to land matters, as stipulated in Article 2 paragraph (2) of Government Regulation Number 37 of 1998 as amended by Government Regulation Number 24 of 2016 concerning the Amendment to Government Regulation Number 37 of 1998 on the Regulation of the Position of Land Deed Officials. One of the authorities of a PPAT in drawing up land-related deeds is the preparation of a Sale and Purchase Deed. In preparing a Sale and Purchase Deed, the PPAT must comply with the prevailing legal provisions. In Supreme Court Decision Number 3507 K/Pdt/2023, the Sale and Purchase Deed drawn up by the PPAT was deemed legally defective and null and void by operation of law, as the deed was made without the knowledge of the rightful landowner.